Fiery Searcher, Caterpillar Hunter Calosoma scrutator (Fabricius 1775) (Insecta: Coleoptera: Carabidae) - Ann Marie Carias; Andrea Lucky (EDIS, 2017)
This EDIS publication is an alternate version of a page published first on the Featured Creatures website. The Featured Creatures collection provides in-depth profiles of insects, nematodes, arachnids and other organisms relevant to Florida. These profiles are intended for the use of interested laypersons with some knowledge of biology as well as academic audiences. This 4-page fact sheet that discusses the fiery searcher beetle was written by Ann Marie Carias and Andrea Lucky, and published by the UF Entomology and Nematology Department, May 2017.